The effect of local government revenue on capital expenditures with economy growth as moderating - Lutfiana Dewi Saputri; Zulfikar (Proceeding International Conference on Accounting and Finance, 2023)
The goal of this study is to see if local government revenue, which includes Local Own-source Revenue, General Allocation Fund, and Special Allocation Fund, has an influence on capital expenditures using Economic Growth as a moderating variable. By gathering data using the documentation study approach, a sample was formed based on the criteria of districts and cities with Local Government Budget reports for 2018-2021. Data analysis techniques include multiple linear regression and moderated regression analysis. The results of the study found that there was an influence between Local Own-source Revenue, general allocation funds on capital expenditures, while special allocation funds and economy growth had no effect on capital expenditures. Economic growth cannot moderate the relationship between Local Own-source Revenue and capital expenditures, but can moderate the relationship between general allocation funds and special allocation funds to capital expenditures.